Aggregation, adherence, anti-adhesion and antagonistic activity properties relating to surface charge of probiotic Lactobacillus brevis gp104 against Staphylococcus aureus. (October 2020) - Hojjati, Mohammad; Behabahani, Behrooz Alizadeh; Falah, Fereshteh
Abstract: Positive effects of fermented foods consumption on humans have stimulated lots of research attention. In this study, we investigated the probiotic potentials, antagonistic activities, and safety properties of Lactobacillus brevis gp104 isolated from Iranian traditional cheese. The results showed that the strain had high resistance to acidic conditions, simulated gastric and intestinal fluid. L. brevis gp104 was able to assimilate cholesterol from the medium; 41% in medium without bile salts and 58% in medium with bile salts. The potential of this strain was relatively low in phytate hydrolyzation and 62.02% hydrophobicity, 40.2% auto-aggregation, and 48.3% co-aggregation were observed. The adhesion value of L. brevis gp104 to adenocarcinoma Caco-2 cells was 13.4% that was also confirmed by scanning electron microscopy (SEM). Antibacterial effect of L. brevis fg104 was imposed against pathogenic strains ( Escherichia coli ATCC 25922, Pseudomonas aeruginosa PTCC 1707, Salmonella typhimurium PTCC 1609, and Staphylococcus aureus ATCC 25923) and the most sensitive strain S. aureus . L. brevis gp104 was able to compete (52%), inhibit (47%) and displace (21%) the adhesion of S. aureus to Caco-2 cells. L. brevis gp104 did not show haemolytic or DNase activity, which confirms its safety aspects. Therefore, L. brevis gp104 was demonstrated promising properties for its potential health benefits for its application as novel bio-therapeutic and bio-preservation agents. Highlights: Lactobacillus brevis gp104 showed high adhesion, hydrophobicity, and auto-aggregation. L. brevis gp104 inhibited the adhesion of pathogens to an intestinal cell line. L. brevis gp104 showed high cholesterol assimilation in the media with and without bile salt.